Ritorno al teatro. Napoli e il medium fotografico: Donato, Biasiucci, Accetta - Fiorentino, Giovanni (Rivista di studi di fotografia. Journal of Studies in Photography, 2016)
This article discusses the “photo-theatrical” approach as a distinguishing element of Neapolitan and Italian photography, in contrast to the so-called “theatralisation” affecting recent trends in the medium. In the lively cultural scene of 1960s Naples, theatre and the performing arts began to influence a specific strand of photographic practice that is still recognisable to this day. The creative strategies elicited by this approach are best seen in the works of Fabio Donato, Antonio Biasiucci, and Cesare Accetta, who have been among the first practitioners in this field.